Sistem Informasi Pelaporan dan Pencatatan Aktifitas Kegiatan Hutan di Taman Nasional Gunung Ciremai Berbasis Image Geotagging - Iwan Lesmana; Yati Nurhayati (NUANSA INFORMATIKA, 2020)
Current advances in information technology, especially cellular phones, have become tools that can facilitate the dissemination and delivery of information from one party to another. The concept of geotagging is very similar to marking points on GPS devices, geotagging not only adds waypoints but also adds spatial metadata information to digital media or photos. The process of reporting and recording activities is still using manual processes, both recorded and unrecorded and there is no system for save the reporting process. The system design in this study is an information system that can be accessed by the public in the form of reporting geotagging images on an android application (.apk) and integrated management by Balai TNGC. Achievements or research targets to be achieved are the ease of delivery of information from the community or TNGC officers in terms of reporting and recording of forest activities and the wishes of the authors are expected to be a pilot or reference that can be used by all National Parks in Indonesia. The system development in this study uses the Extreme Programing (XP) method, where this method is suitable for the existing problems. For modeling design using UML (Unified Modeling Language.Keywords: TNGC; Geotagging; Android; Extreme Programing; UML